Años potenciales de vida perdidos por la población de Medellín, 1994-1996 (1999)
ABSTRACT: The study shows the magnitude and distribution of the potencial years of life lost by the population of Medellín during 1994-1996 by different grouping of causes, age, sex and socioeconomic stratum. The source of the data was the death registry run by the DANE that has a coverage close to 100%; almost 50% of the potencial years of life lost was due to intentional injury; also, accidental injury, perinatal causes, cardiovascular diseases and malign neoplasmas ranked first among the various subgroups of causes. Large differences were detected in the population average of potencial years of life lost among the different socioeconomic strata, the low one having the highest. Some strategies for prevention and health promotion are proposed that should be implemented in the low socioeconomic strata as a top priority.